Implementasi Pengelolaan Keuangan Negara Dalam Perspektif Ekonomi Islam (Studi APBN 2009-2017) - Sazali, Munawir (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2020)
The focus of this study is to determine the implementation of state financial management after the enactment of law number 17 of 2003 on the management of state finances in Indonesia (APBN) managed by the government in the period 2009-2017 as seen from the level of poverty, unemployment and external debt country to the impact of the management of the state budget over a period of 9 years which was examined through an Islamic economic perspective. The methodology used is a qualitative approach to Islamic economics and the analysis used is descriptive analysis. The data used are primary and secondary data. The results of this study indicate that the management of state finances in Indonesia after the enactment of Law No. 17 of 2003 there is a change in budget transparency and efficiency of budget use but there are undesirable impacts of poverty, unemployment and foreign debt that are still high, and the role of Islamic economics that must be optimized in the future is to help economic growth in Indonesia, in this case through the National Amil Zakat Agency and the Amil Zakat Institution.